Features of the Phase Transition in Ni50.9Мn29.43Gа19.67 Single Crystal - Y.B. Skirta; A.L. Sozinov; V.V. Nevdacha (Журнал нано- та електронної фізики)
The temperature dependences of the linear sizes, electrical resistance, and magnetic permeability in Ni50.9Мn29.43Gа19.67 single-crystal in the area of martensitic transformation were measured. The values of jumps of the above mentioned characteristics during martensitic transition depend on the crystallographic direction and ratio between structural domains and c-, and а-, b-axes along this direction.